Uma discussão crítica sobre ambientes periféricos e políticas públicas baseadas em arranjos produtivos locais (APLs) - Rafaella Stradiotto Vignandi (2017)
This thesis sought to intrinsically analyze the implementation and evolution of the format of local development public policies for Brazil based on Local Productivity Arrangements (LPA). Firstly, a discussion was made concerning clustering, Local Productivity Arrangements and their interconnections with Network theories. This aimed contextualize the functioning of cluster dynamic and LPAs according to economists and public politics developers directed to the local and regional growth. At a second moment, an explanation about the local and regional theories was brought directed at the potential meaning of local and regional development and territory competitiveness created from the new local and regional development theories. Afterwards, the contextualization of peripheral environments were presented as essential conditions to contemporary restrictions, stressing the center-periphery dubiousness and equity of regional development and the periphery changing process upon a new recent perspective of economic and regional development processes. The analytical answers to this studied process were done twofold. The first part was a construction of an index formally developed aiming the space insertion in measuring, which presented Compound Concentration Index (CCIs). The second one is an explanatory description of the selected variables for analyses of the evolution of public policies of LPAs in a nation context, in which it was considered some social-economic conditions more important to portray the countries considered as peripheral, which is Brazils case. The results of the first part confirmed a loss in value in sub-indexes which comprise (CCIs), both in traditional versions as well as in pondered spatial versions of average productivity specialization(QL and QLs), HerfindahlHirschman Index (HHm and HHms) and relative participation (PR and PRs). Besides, it was observed the agglomerative spatial effects via neighboring effects which confirmed an important influence over the studied sub-indexes, revealing that the productive dynamic of a place depends on some productive standards of the economic activities performed by it. The obtained results through (CCIs) for the three spatial scales considered (meso-regions, micro-regions and municipalities) were that the less aggregated the spatial measures were, the higher the value indexes became, and in relation to concentration, it went from less concentrated to more concentrated, except in the case of micro-regions in which the scale is more sensitive. The localization and identification of the concentration of activities for each agglomerate sectors of Brazilian municipalities measured by the CCIs for Transformation Industry (section C), for Commerce, Automobile Vehicle and Motorcycle Repair (section G), and for Public Management, Defense and Social Security (section O) also presented great local inequality concerning compound concentration quite relevant to the analyses. Finally, through thorough analyses of the municipalities which received and the ones which did not receive the policy, it was not possible to clearly identify if the incentive public policy to LPAs in Brazil provided efficient solutions to the places which received them. The objects of analyses enabled us to consider through social-economical conditioning the Brazilian municipality specificities and understand better how this local reality presented itself throughout the years. It was also possible identify a lack of meaningful territorial and spatial equity, strategic actions and clear guidelines which help peripheral regions to foster their local potential and reduce the existing regional inequalities.